The need for invasive cardiological assessment and operation: viewpoint of a district general hospital. Issue 5 (May 1986) - Cripps, T; Dennis, M S; Joy, M
Abstract : The uptake of cardiac catheterisation and operation and of permanent pacemaker implantation in a district hospital in Surrey from 1979 to 1984 was studied prospectively. The 1982-84 figures for coronary artery operation indicated that 362 procedures/million population/annum were needed in the district. If patients with greater than or equal to New York Heart Association grade II angina only received operation the corresponding figure would have been 325. The national need for these procedures (464/million population/year) was estimated by correcting for the low standardised mortality ratio for ischaemic heart disease in the health district that was studied. Valvular heart disease accounted for 79 operations/million population/annum and permanent pacemaker insertion for 87 procedures/million population/annum. These figures underline the substantial shortfall in modern cardiac care in the United Kingdom.